Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.3390/molecules24061114
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Profiling of Pitaya (Hylocereus polyrhizus) during Fruit Development and Maturation

Abstract: Pitaya (Hylocereus polyrhizus) has attracted much interest from consumers as it is a novelty fruit with high nutrient content and a tolerance to drought stress. As a group of attractive pigment- and health-promoting natural compounds, betalains represent a visual feature for pitaya fruit quality. However, little information on the correlation between betalains and relevant metabolites exists so far. Currently, color (Commission International del’Eclairage, CIE) parameters, betalain contents, and untargeted met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
49
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(57 citation statements)
references
References 58 publications
5
49
1
2
Order By: Relevance
“…and explore the role of anthocyanins in color formation. Fruits at 30 days after flowering were harvested and used in this study because color change mainly occurs at this stage [19]. Although previous studies investigated the metabolome of Hylocereus spp.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…and explore the role of anthocyanins in color formation. Fruits at 30 days after flowering were harvested and used in this study because color change mainly occurs at this stage [19]. Although previous studies investigated the metabolome of Hylocereus spp.…”
Section: Discussionmentioning
confidence: 99%
“…Betalains have been extensively characterized in pitayas [15][16][17][18][19]. Betalains are only found in some species of Caryophyllales and include betacyanin (red-purple) and betaxanthins (yellow) [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polturak et al (2018) ascertained that the loss of anthocyanin production in the Caryophyllales may be rooted in several evolutionary events, including mutation of anthocyanin biosynthetic genes, rather than the downregulation of anthocyanin pathway genes. Wu et al (2019) found that the contents of betalains dramatically increased along with the emergence of pigment at color-broken stages in 'Zihonglong' pulp. The number of pigmented cells and the concentration of pigment in fruit tissue affect the fruit color directly, in present research, it was obvious that the pigmented cells in pulp emerged along with a peak value of citramalic acid at color-broken stage, hence, we hypothesized that citramalic acid may contributed to the formation of betalain pigments in red pulp pitaya.…”
Section: Discussionmentioning
confidence: 94%
“…To gain the chemical markers for discrimination of the three groups in the PLS-DA model, VIP values were calculated and inspected for identified volatile compounds. Generally, VIP values > 1 and p < 0.05 are considered as significant contributors to the model [40,50,51]. In this study, seven-fold cross-validation and 200 response permutation testing (RPT) methods were used to investigate the quality of the model.…”
Section: Discussionmentioning
confidence: 99%